AIR - Laforet, Vincent; Pettit, Donald R. (Chicago, Illinois : Press Syndication Group, 2016)
A collection of aerial photographs of New York City, Chicago, Los Angeles, Las Vegas, Berlin, London, Miami, San Francisco, Barcelona and Sydney, taken by photographer Vincent Laforet from altitudes between 5,000 and almost 12,000 feet.
New York -- Chicago -- Los Angeles -- Berlin -- London -- Miami -- San Francisco -- Barcelona -- Sydney.
HBK.
Keywords: Cities and towns -- Aerial photographs; Cities and towns -- Pictorial works; Cities and towns; Aerial photographs; Pictorial works; Aerial photographs